The Students’ Perception on Summarizing as Learning Strategy in L2 Reading - Sugesti, Tika Andria; Humaera, Isna (IAIN KENDARI, 2023)
This case study aimed to investigate the students’ perception of summarizing as a learning strategy in L2 reading. The study was conducted at one of the universities in Southeast Sulawesi with data gathered from five students in the fourth semester from the English education department. Reflection documents were used to obtain the data. Through a thematic analysis method, the data were analyzed qualitatively. The findings revealed that the summarizing strategy in L2 reading learning was perceived tend to be positive by most students. As reported by participants, summarizing strategy provided advantages for enhancing the L2 reading learning process. Moreover, numerous barriers faced by students in the summarizing process were also conveyed in the findings of this study. It implies that this strategy can be an alternative for L2 reading class as the students prefer this strategy as well.Keywords: Learning strategy; perception; summarizing.